UPAYA PENINGKATAN HASIL BELAJAR KIMIA SISWA KELAS X DPIB A SMK N 1 PAJANGAN MELALUI PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Sugiarti, Sugiarti (INCARE, International Journal of Educational Resources, 2021)
This research is motivated by the lack of students who are actively involved in learning, students feel less interested in chemical learning because the material is difficult to understand, thus causing low student learning outcomes. This research aims to reduce the burden of students who have low ability and for students who have high abilities can further improve their abilities by guiding and motivating their group mates, in addition, the application of STAD-type cooperative learning models is expected to attract students' attention so as to encourage students to get maximum learning outcomes. This research was conducted in August to November 2019 at SMK Negeri 1 Display. The subject of this study was class X DPIB A as many as 30 students. This class action research procedure uses these using 2 cycles each cycle consisting of 2 encounters. Each cycle consists of planning, execution, observation, reflection. Indicators of the success of this study are an increase in student learning outcomes, namely at least 80% of students get grades more than or equal to 75, and at least 50% of students actively follow the learning. The results showed that the use of STAD-type cooperative learning models could improve students' chemical learning outcomes from 56.7% in cycle 1 to 83.3% in cycle 2. The average grade of students' chemistry learning outcomes increased from 66.83 in cycle 1 to 79.33 in cycle 2. It can also increase student learning activities from 66.77% to 81.50%.